CRITICAL OUTLOOK AT SPECIAL ECONOMIC ZONE IN ASIA: A COMPARISON BETWEEN INDONESIA, MALAYSIA, THAILAND AND CHINA - Sari Wahyuni; Esther Sri Astuti; Karina Miaprajna Utari (Journal of Indonesian Economy and Business (JIEB), 2013)
Special Economic Zones (SEZ) have been proven to help countries in fostering economicgrowth. The aim of this research is to try to help the government to improve SEZ policies inIndonesia by providing a benchmark with other SEZ countries in China, Malaysia, andThailand. While China has the most established SEZ program, Malaysia and Thailand alsohave highly-regarded SEZs and investment incentives. These neighboring countries havedeveloped SEZs in significant quantities but the greatest returns have come from a subsection oflarge-scale zones with favorable locations, good planning and access to resources. Thailandhas a smaller number of zones, but a higher rate of successful zones, such as the automobilecluster which became the anchor of automotive production in Asia. How Indonesia’s positioncompares to these three Asian countries is the main question of this study.Keywords: special economic zone, foreign investment, benchmarking, competitiveness, China,Malaysia, Thailand